Morphometric Parameters of Peripheral Nerves in Calves Correlated with Conduction Velocity. (13th January 2014) - Schenk, H.C.; Haastert‐Talini, K.; Jungnickel, J.; Grothe, C.; Meyer, H.; Rehage, J.; Fehr, M.; Bokemeyer, J.; Rohn, C.; Tipold, A.
<x xml:space="preserve">Abstract</x> Background Peripheral nerve injuries are the most frequent neurologic disorder in cattle. So far, no physiologic values have been established for the motor nerve conduction velocity (mNCV) in this precocial species. Objectives The electrophysiologic and morphometric reference values of peripheral nerves in calves were determined. It was hypothesized that these parameters would correlate to the high degree of maturity in the first days of life in this species compared to other species. Animals Twenty‐six healthy calves were used in this study. Methods The mNCV of the radial and the sciatic/common peroneal nerve was measured in all 26 calves. Nerve biopsies from a group of 6 calves were taken to correlate the obtained electrophysiologic data with morphological parameters. Results The mean mNCV of the radial nerve was 48.3 ± 10.6 m/s, whereas the mean mNCV of the sciatic/peroneal nerve was with 83.8 ± 5.9 m/s significantly faster (P < .0001). The average fiber diameter was 8.40 ± 2.80 μm (range, 1.98–17.90 μm) and the average g‐ratio was 0.61 ± 0.04 SD. Conclusion and Clinical Importance The established reference values for mNCV in calves correlate well with the evaluated morphometric parameters. Attributable to their comparably fast mNCV and high fiber diameters, juvenile calves appear to be much more mature individuals than other mammals. Electrophysiologic characterization of peripheral nerve injury now is feasible in this species.